Visualizing cancer and response to therapy in vivo using Cy5.5-labeled factor VIIa and anti-tissue factor antibody. (April 2015) - Zhu, Shijun; Kisiel, Walter; Lu, Yang J.; Petersen, Lars C.; Ndungu, John M.; Moore, Terry W.; Parker, Ernest T.; Sun, Aiming; Sarkaria, Jann N.; Snyder, James P.; Liotta, Dennis C.; Brat, Daniel J.; et al.
Abstract We have developed a specific technique for imaging cancer in vivo using Cy5.5-labeled factor VIIa (fVIIa), clotting-deficient FFRck-fVIIa, paclitaxel-FFRck-fVIIa, and anti-tissue factor (TF) antibody. FVIIa is the natural ligand for TF. We took advantage of the fact that vascular endothelial cells (VECs) in cancer, but not normal tissue, aberrantly express TF due to its induction by vascular endothelial growth factor (VEGF). Under physiological conditions, TF is expressed by stromal cells and outer blood vessel layers (smooth muscle and adventitia), but not by VECs. We hypothesized that labeled fVIIa or anti-TF antibodies could be used to image the tumor vasculature in vivo. To test this, Cy5.5-labeled fVIIa, FFRck-fVIIa, paclitaxel-FFRck-fVIIa, and anti-TF antibody were developed and administered to athymic nude mice carrying xenografts including glioma U87EGFRviii, pancreatic cancer ASPC-1 and Mia PaCa-2, and squamous cell carcinoma KB-V1. Cy5.5 labeled with these targeting proteins specifically localized to the tumor xenografts for at least 14 days but unconjugated Cy5.5 did not localize to any xenografts or organs. This method of imaging TF in the tumor VECs may be useful in detecting primary tumors and metastases as well as monitoring in vivo therapeutic responses.